Housing and Urbanism in Spain in Francoist period: Public policies and propaganda around the Obra Sindical del Hogar (1939-1977) - Pérez-Eguíluz, Victor; Jiménez Jiménez, Marina; Fernández-Maroto, Miguel; Santos y Ganges, Luis (International Planning History Society Proceedings, 2022)
The Obra Sindical del Hogar —OSH, Housing Trade Union Welfare— was a Spanish social housing building entity during the Francoist dictatorship. Although it served the Instituto Nacional de la Vivienda—INV, National Housing Institute—, which was the autonomous state agency for housing policy, OSH was under the control of FET y de las JONS, which was the only party of Franco’s regime. This paper aims to compare real performance of OSH with its own propaganda throughout the dictatorship. Our methodology has included analysing housing production data at the national level in this period, particularly social housing, and studying three significant and complementary projects carried out in three locations in the region of Castilla y León in three different decades —Burgos in the forties, Covaleda (Soria) in the fifties and Valladolid in the sixties—. It can be concluded that the OSH performed a huge propaganda work that made its production seem much larger than it really was.